Oral surgery in patients with classic and direct oral anticoagulants: a literature review - Alfaro Pacheco, Carlos (2025)
For decades, vitamin K antagonists such as warfarin have been the standard anticoagulant treatment, despite the clinical management challenges they present. In contrast, direct oral anticoagulants (DOACs) offer fewer complications and therapeutic advantages. These are classified into thrombin inhibitors (dabigatran) and factor Xa inhibitors (rivaroxaban, apixaban, edoxaban). Approximately 10% of anticoagulated patients will require some form of surgery, including oral surgery. In this context, the objective of this review was to update oral surgical management in anticoagulated patients and to familiarize dentists with protocols for warfarin and DOAC users. Discontinuing anticoagulant therapy carries significant and even fatal risks, which in many cases outweigh the benefits of reducing bleeding during oral surgery. It is concluded that anticoagulant therapy should only be suspended for procedures with a high risk of bleeding, and it is essential to evaluate the bleeding risk of the procedure beforehand and apply hemostatic measures when necessary.